DYNAMICS OF CROPPING PATTERN IN KRISHNA ZONE OF ANDHRA PRADESH- MARKOV CHAIN APPROACH. - G RAGHUNADHA REDDY*, M CHANDHRASEKHAR REDDY, K PRAVALLIKA AND B MEHER GITA (The Journal of Research ANGRAU, 2022)
The cropping pattern plays a vital role in determining the level of agricultural production andreflects the agricultural economy of an area or region. The present study was conducted to know thechanges in the cropping pattern of the Krishna zone of Andhra Pradesh using Markov chain analysis.Time series data on the area under different crops grown from the period 2000-01 to 2019-20 werecollected and analyzed for 3 districts in the Krishna zone separately for kharif and rabi seasons. Theresults revealed that in the Krishna district, blackgram retained 88 per cent in rabi season and just6.9 per cent in kharif season. Maize as an emerging crop retained more than 75 per cent of its sharein both Krishna and Guntur districts. Redgram being a kharif crop, retained 37.5 per cent in Krishnadistrict and its retention was more in Guntur (57.5 per cent) and Prakasham district (63.8 per cent).At zonal level redgram retained 45.1 per cent of its previous acreage. Zonal level retention valuesrange in between their district wise retention. A high degree of substitutability was noticed betweentwo commercial crops i.e, cotton and chillies. Paddy has emerged as one of the stable crops in allthree districts irrespective of the season. Greengram’s ability to retain its area was less in the studyperiod.